2021
DOI: 10.1097/01.asw.0000756512.87211.13
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Wound Complications after Colorectal Surgery with Single-Use Negative-Pressure Wound Therapy Versus Surgical Dressing over Closed Incisions: A Randomized Controlled Trial

Abstract: BACKGROUND Global studies indicate that surgical site infections (SSIs) are a major healthcare challenge within hospitals and can have a profound impact on patient quality of life and healthcare costs. Closed-incision negative-pressure therapy (ciNPT) has been reported to provide positive clinical benefits for patients with various incisions, including those following colorectal surgeries. METHODS Investigators performed a prospective, randomized, multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 14 publications
(36 reference statements)
0
23
0
Order By: Relevance
“…The 84 studies identified encompassed cardiac surgery (n = 8), general abdominal surgery (n = 21), obstetric and gynecologic surgery (n = 8), orthopedic surgery (n = 16), plastic surgery (n = 16), and vascular surgery (n = 15). 11–16,20–97…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 84 studies identified encompassed cardiac surgery (n = 8), general abdominal surgery (n = 21), obstetric and gynecologic surgery (n = 8), orthopedic surgery (n = 16), plastic surgery (n = 16), and vascular surgery (n = 15). 11–16,20–97…”
Section: Resultsmentioning
confidence: 99%
“…Dressings used in the SOC population varied and included gauze dressings, antimicrobial hydrofiber dressings, absorbent dressings, hydrocolloid dressings, occlusive dressings, or foam dressings. 11–16,20–97…”
Section: Resultsmentioning
confidence: 99%
“…The number of patients per RCT ranged between 40 [ 33 ] and 505 [ 32 ]. Studies were published recently, one in 2016 [ 21 ], two in 2017 [ 18 , 20 ], two in 2019 [ 17 , 19 ], three in 2020 [ 30 , 31 , 33 ] and three in 2021 [ 29 , 32 , 34 ]. Four RCTs were performed in the USA [ 17 , 21 , 32 , 33 ], two in Australia [ 31 , 34 ], two in Spain [ 29 , 30 ], one in Canada [ 19 ], one in Ireland [ 20 ] and one in China [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies were published recently, one in 2016 [ 21 ], two in 2017 [ 18 , 20 ], two in 2019 [ 17 , 19 ], three in 2020 [ 30 , 31 , 33 ] and three in 2021 [ 29 , 32 , 34 ]. Four RCTs were performed in the USA [ 17 , 21 , 32 , 33 ], two in Australia [ 31 , 34 ], two in Spain [ 29 , 30 ], one in Canada [ 19 ], one in Ireland [ 20 ] and one in China [ 18 ]. Four RCTs included patients who underwent abdominal/digestive surgery [ 18 , 20 , 21 , 31 ], two included patients who had hepato-biliary surgery [ 17 , 33 ], two included patients who underwent colorectal surgery [ 19 , 29 ], one included patients who had incisional hernia repair [ 30 ], one included patients who underwent laparotomy for gynaecologic surgery [ 32 ], and one included patients who had general surgery [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation